Proyecto de cambio en el destino de una obra pía (de la enseñanza del latín a la dotación de becas universitarias) (2016)
This article contains a detailed historical study about teaching Latin in Asturias during the sixteenth century, carefully documented in the historical archives of Oviedo which is the place to which this paper is addressed; for this reason it contains some literal paleographic transcriptions of ancient texts that illuminate the issue and, undoubtedly, offer a contribution to the teaching of Philosophy and Theology. It is to be clarified that the citation varies in this text because, mostly, they are ancient documentary sources that are found in historical archives.